Uttarakhand Himalayas harbour rich diversity of indigenous and minor vegetables - Mishra, A C; Bhatt, Lalit; Dubey, R. K. (Indian Horticulture, 2020)
All indigenous and minor vegetable crops are grown for domestic consumption and even many of them have not been brought under systematic cultivation. The farmers use to save their own seed of the crops which are in cultivation and grow in subsequent years and thus, crops always remain under thrust and underutilized. For exploitation of the potential of these traditional and indigenous vegetable crops of Himalayan regions, an intensive research work is needed for identification of nutraceuticals rich promising types, development of high yielding and stress tolerant varieties, agronomical packages of practices and seed chain system.